THE RELATIONSHIP BETWEEN THE ORGANIZATIONAL STRUCTURE AND IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT IN GOVERNMENTAL HOSPITALS IN THE WEST BANK, PALESTINE - Maen Mohammad Salih Alqam (My University, 2023)
Abstract Introduction: The purpose of this study is to consider the relationship between the organizational structure and the implementation of total quality management in government hospitals in the West Bank, Palestine. To identify the degree of the application of total quality management in government hospitals in the West Bank, Palestine. Methodology: To identify the most influential organizational structural areas in the components of total quality management. A well-structured questionnaire was used as a data collection tool consisting of questions related to the structure of the organization and about the components of TQM, which was distributed to each employee with an administrative title from various job categories. Results: After the collection of information, using SPSS25, the researcher presented an analysis to address the issues and confirm or deny the hypothesis. The results show that it is evident that organizational structure has an impact on and a significant relationship with TQM implementation in Palestinian government hospitals. Conclusion: It came to light that OS has an impact on how TQM and its elements are implemented. According to regression analysis, workgroups have an adverse impact on the implementation of TQM, whereas formality makes the greatest contribution. Keywords: Total quality management; organizational structure; hospitals; relationship; implementation.